2021
DOI: 10.2147/dddt.s286297
|View full text |Cite
|
Sign up to set email alerts
|

Gypenosides Inhibit Inflammatory Response and Apoptosis of Endothelial and Epithelial Cells in LPS-Induced ALI: A Study Based on Bioinformatic Analysis and in vivo/vitro Experiments

Abstract: Introduction: Severe inflammatory response leads to poor prognosis of acute lung injury (ALI), the role of gypenosides (GPs) on ALI is not fully clear. The study aimed at investigating the effects of GPs on ALI. Methods: We firstly established LPS-induced ALI mice model. Then, we tested whether GPs contributed to alleviate inflammatory response and lung injury of ALI in vivo. In order to identify specific mechanisms of the phenomenon, we conducted a bioinformatic analysis of LPS-induced ALI mice based on GEO d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 42 publications
(58 reference statements)
0
14
0
Order By: Relevance
“…LPS challenge also gives rise to apoptosis of pulmonary epithelial cells, the inhibition of which is important for maintaining pulmonary function [ 17 ]. Herein, we detected the makers of apoptosis in LPS-treated lung tissues.…”
Section: Resultsmentioning
confidence: 99%
“…LPS challenge also gives rise to apoptosis of pulmonary epithelial cells, the inhibition of which is important for maintaining pulmonary function [ 17 ]. Herein, we detected the makers of apoptosis in LPS-treated lung tissues.…”
Section: Resultsmentioning
confidence: 99%
“…HUVEC dysfunction and morphological damage can manifest as multiple physiological effects, including adhesion of leukocytes, vasoconstriction, platelet activation, oxidative stress, and inflammation, which ultimately lead to the development of AS. Therefore, promoting HUVEC proliferation, inhibiting HUVEC apoptosis, and suppressing HUVEC inflammation have become key strategies for the prevention and control of AS [ 9 , 16 ]. Undoubtedly, macrophages are the primary concern in the treatment of HUVEC cell injury.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have demonstrated that the development of ALI is related to inflammation, oxidative stress, apoptosis, and cellular immunity. [16][17][18][19] However, mortality due to ALI continues to be high. There are many published reports on the activity of natural products to treat ALI.…”
Section: Discussionmentioning
confidence: 99%